Precautions For Jakarta-Bandung High-Speed Rail Infrastructure Project Cooperation: Construction At Night And In Storm - Wawan Riyanta (P3M- Politeknik Negeri Kupang, 2023)
The Jakarta-Bandung high-speed rail infrastructure project delays cause the financial burden in the form of interest during construction to swell KCIC had to improve project performance by carrying out construction at night and must improve strategies for dealing with Indonesian extreme weather. Before construction at night, strict inspection shall also be focused on lighting lamps. Construction personnel shall prepare flashlights, searchlights, all parts and components shall be carefully inspected in strict accordance with relevant regulations to ensure the normal operation of the equipment. During the flood season, the construction personnel of large-scale railway maintenance machinery shall strictly implement the measures for safe driving in the flood season issued by the Ministry of railways. the construction staff shall report the disaster and dangerous situation to the attendant of the nearest station through the train dispatching station in time. When large-scale railway maintenance machinery encounters strong wind, rainstorm, Blizzard and other difficulties or unknown conditions during construction and operation, it shall immediately stop construction and slow down, and timely report the situation to the station. Keyword: KCIC, Construction, Railway, Maintenance.